Comparative evaluation of fracture resistance of endodontically treated teeth with epoxy resin-based sealers AH plus and mineral trioxide aggregate fillapex: An in vitro study - Anika Mittal; Shifali Dadu; Paridhi Garg; Bidya Yendrembam; Anju Abraham; Kulshrest Singh (Indian Journal of Dental Sciences, 2017)
Aim: This study aims to evaluate and compare the fracture resistance of endodontically treated teeth obturated with gutta-percha using two sealers, AH Plus, and mineral trioxide aggregate (MTA) Fillapex. Materials and Methods: Twenty single-rooted mandibular premolars, decoronated at cementoenamel junction, were divided into two groups (n = 10 each). Cleaning and shaping of root canals were done using ProTaper rotary files and 3% sodium hypochlorite irrigation. Obturation was done using sealers, AH Plus (Dentsply, Germany) in Group 1 and MTA Fillapex (Angeles, Brazil) in Group 2 and gutta-percha. The teeth were subjected to vertical loading using a universal testing machine, and the readings were recorded at the point at which fracture of the roots occurred. The data were subjected to statistical analysis followed by pairwise comparison using Tukey's post hoc test. Results: According to the study, it was found that AH Plus showed better fracture resistance than MTA Fillapex. Statistically, no significant difference was found between the two groups. Conclusion: AH Plus and MTA Fillapex gave comparable results as root canal sealers.